’n Spieël vir die predikant - Deel II - Vos, Casparus Johannes Adam (Verbum et ecclesia, 1998)
A mirror for the minister This article focusses primeraly on the church as well as the minister as servant. A servant ministry enables the minister to be a witness in and to the world. The following features of this ministry can be distinguished: integrity, enthusiasm, truth as a lifestyle, humility and service.